The Mitigation Training of Urban Conflagration in RW 04 Harjamukti Subdistrict - Indah Puspita Sari; Qisti Luffiah Kurata Ayuni; Chindy Respa; Isa Elfianto; Nur Rahmi Fajri Yanti; Aan Hidayat (Prospect Publishing, 2025)
The case of urban fires needs to be a concern in Depok City. Considering the vulnerability of fire disaster cases, it is necessary to reduce the impact of disasters, which is commonly called disaster mitigation. One example of measures to reduce community vulnerability to fire disasters is through mitigation training. The possibility of a fire disaster with a high-risk scale in Harjamukti Village can significantly impact citizens in densely populated settlements, one of which is RW 04, an area with these characteristics. Therefore, PT Perusahaan Gas Negara, Tbk. - Offtake Stasiun Cimanggis initiated The Mitigation Training of Urban Conflagration in RW 04, Harjamukti Subdistrict, Cimanggis District, Depok City. The purpose of this training was to empower the community with basic skills in emergency fire disaster situations. This training technically contained 3 stages, including preparation, implementation, and evaluation stages. The training methods included lecturing and practicing in a one-day activity attended by 44 participants. It was expected that with the new knowledge and skills, the community could be more proactive in preventing and mitigating fire disasters, thus mitigating the potential for greater losses.